2018
DOI: 10.1002/pssb.201800306
|View full text |Cite
|
Sign up to set email alerts
|

The Magnetic, Electronic, and Thermodynamic Properties of High Entropy Alloy CrMnFeCoNi: A First‐Principles Study

Abstract: A theoretical investigation into the electronic and thermodynamic properties of the high entropy alloy CrMnFeCoNi in nonmagnetic (NM) and ferrimagnetic (FIM) states based on first-principles calculations has been implemented. Compared with the NM state, there is an obvious localized distribution of charges between Cr and Mn atoms with the lower valence electronic concentration (VEC) in the FIM state, showing covalent characters. Different spin-polarized behaviors in compositional atoms have been proposed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Several methods have been employed to describe HEAs on the electronic scale 66 , including the virtual crystal approximation (VCA) 12 , coherent potential approximation (CPA) 67 , special quasi-random structures (SQS) 14,[68][69][70][71][72] , and molecular dynamics (MD) based methods [73][74][75] . Only a few studies have assessed the thermal conductivity of HEAs, using semi-empirical MD 76,77 .…”
Section: Alloys -Using High Entropy Alloys As a Test Casementioning
confidence: 99%
“…Several methods have been employed to describe HEAs on the electronic scale 66 , including the virtual crystal approximation (VCA) 12 , coherent potential approximation (CPA) 67 , special quasi-random structures (SQS) 14,[68][69][70][71][72] , and molecular dynamics (MD) based methods [73][74][75] . Only a few studies have assessed the thermal conductivity of HEAs, using semi-empirical MD 76,77 .…”
Section: Alloys -Using High Entropy Alloys As a Test Casementioning
confidence: 99%
“…22,23 TMHEAs are formed by mixing various metallic elements and have specific physicochemical characteristics, such as outstanding magnetic and electrical properties, and high thermomechanical stability when the size is decreased to nanometer range. 24,25 Also, TMHEAs exhibit more redox active sites, and their three-dimensional diffusion channels aid towards the easy flow of the electrolyte, 16 almost ending the limitations of poor cycling stability and material degradation during electrochemical tests. In this regard, various TMHEAs and their oxides have been studied with different morphologies, such as nanoporous, 26 quasi spherical, 27 and nano agglomerations, 28 along with some HEA composites, such as rHEA-CNT, 29 MnO 2 -FeCrCoMnNiAl 0.75 , 30 and HEAnitrides, 31 for supercapacitor applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, the small system sizes accessible in DFT calculations can drastically affect the many-body correlations and the entropy of mixing. [2] On the other hand, in the case of stainless steel (consisting of Cr, Fe, Mn, Mo, and Ni), Wang et al [14] reported that vibrational entropy contributions are higher than TDS ideal at temperatures above 600 K. At temperatures less than 600 K, even though the configurational entropy calculated is higher than the other contributions, it is not clear if this is valid for the actual configurational entropy contribution, which is supposed to be lower than DS ideal . Thus, a systematic analysis of the temperature dependence of the short range order and the configurational entropy is also important because many solid solution HEA design guidelines that use DS ideal have been proposed in the literature.…”
mentioning
confidence: 99%